The Meaning of Happiness and Religiosity for Pre-Prosperous Family: Study in Manado, Bandar Lampung, and Yogyakarta - Ahmad Rajafi; Naili Adilah Hamhij; Suyatno Ladiqi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2020)
The results of this research (2017) want to explain the correlation between happiness and religiosity for poor families. The locus of this research is in the city of Manado, North Sulawesi Province, Bandar Lampung City, Lampung Province, and Yogyakarta City in Yogyakarta Special Region Province. This research is important because there is an assumption in the community that even poor people who are religious are certainly not happy. This assumption is further answered in this study, where there is a positive and significant relationship between happiness and religiosity in poor families in Yogyakarta, but not for Manado and Bandar Lampung. The highest level of happiness is in the city of Yogyakarta and the highest level of religiosity is in the city of Manado. This difference occurs because the concept of happiness for religious poor families in Manado, Yogyakarta and Bandar Lampung has different point of view and has the unique itself.